إشكاليّة تدريس المفردات في برنامج تعليم اللّغة العربيّة للنّاطقين بغيرها في ضوء أساليب التّدريس الحديثة: Teaching Arabic vocabulary in the light of modern teaching methods to non-native speakers - Mohamed WagiAlla, Muna Yousif (SIBAWAYH Arabic Language and Education, 2020)
This study aims to highlight the importance of vocabulary in teaching Arabic to non-native speakers, how to teach, and to identify important problems and the foundations of building criteria for its selection in the light of modern teaching methods. And how the learner can use it in different contexts correctly. The study dealt with the following steps, and that represented the first recitation of what the vocabulary is? What kinds of vocabulary? What are the criteria for selecting vocabulary? How to display vocabulary? What are the methods for teaching vocabulary? What are modern ways of teaching vocabulary? What are the vocabulary teaching methods? There is a presentation next to some previous studies. As for the second aspect, the applied aspect was to analyze the results by unpacking the (corresponding) study tool. The study used the descriptive approach. The most important results are that the way the vocabulary is presented in the curriculum affects the way it is taught, and that there are many problems related to teaching vocabulary, some of which can be addressed by the teacher and others related to the curricula.